NON VERBAL COMMUNICATION IN PUNJABI POP MUSIC VIDEOS: A STUDY OF SELECTED AWARD WINNING SONGS - Kumar, Mohit; Malik, Pawan Singh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research paper delves into the realm of non-verbal communication in Punjabi pop music videos by analyzing selected award-winning songs. The study focuses on music videos that received the Best Music Video or Best Music Video Direction award at the PTC Punjabi Music Awards from 2014 to 2017, namely "Soch" by Hardy. (2014), "Dairy" by Gill (2015), and "Time Table 2" by Billa (2016),. The analysis centers on various non-verbal communication elements, including kinesis, proxemics, oculesics, chronemics, physical appearance, and background music. The objectives of this study are “To scrutinize the application of non-verbal communication elements in Punjabi Pop Music Videos” and “To examine the utilization of background music and sound in conveying non-verbal messages in these videos”.